Benson Relaxation Techniques on Reducing Pain Scale and Sleep Quality in Post Appendectomy Patients - Rahmiwati, Rahmiwati; Juwita, Lisavina; Ramadani, Putri; Dewi, Ratna (PT. Riset Press International, 2024)
Acute pain is pain that arises suddenly and does not last long like post-surgery. Postoperative appendectomy affects the person's sleep quality being disrupted due to the stress and pain. The purpose of this study was to determine the effect of Benson's relaxation on pain scale and sleep quality in post-appendectomy surgery patients. The type of research was quantitative research. It was conducted by experimental research with a quasi-experimental research design with a pretest and posttest design. The population was all postoperative appendectomy patients in the operating room of RSUD Dr. Achmad Mochtar Bukittinggi. By using accidental sampling technique, 20 respondents were chosen as the samples. The data were processed by univariate and bivariate analysis by using the Wilcolxon test on the pain scale and the T Test Dependent test on sleep quality. The average pain score of respondents before the intervention was 2.6 (moderate pain) and the average score after the intervention was 3.9 (pain decreased), while the average quality of sleep before the intervention was 8.4, and the average quality of sleep after the intervention was 5.95. Benson's relaxation has an effect on pain, this is shown by using the Wilcolxon test with a p-value of 0.00 4 ≤ 0.05, and Benson's relaxation has an effect on sleep quality, this is shown by using the Dependent T test with a p- value of 0.000 ≤ 0.05. It can be concluded that Benson relaxation has a significant effect on overcoming pain nursing problems and sleep quality in post-appendectomy surgery patients where there is a decrease in the average pain scale intensity and sleep quality.